2018
DOI: 10.1038/s41598-018-29094-2
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics into outer space: feasibility assessments of encapsulated freeze-dried probiotics during 1 month’s storage on the International Space Station

Abstract: Suppression of immune function during long spaceflights is an issue that needs to be overcome. The well-established probiotic Lactobacillus casei strain Shirota (LcS) could be a promising countermeasure, and we have launched a project to investigate the efficacy of its use on the International Space Station (ISS). As a first step, we developed a specialist probiotic product for space experiments, containing freeze-dried LcS in capsule form (Probiotics Package), and tested its stability through 1 month of stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…The authors did not observe differences between the probiotic flight samples and ground controls regarding the profiles of randomly amplified polymorphic DNA, the sequence variant frequency, the carbohydrate fermentative patterns, the reactivity to strain-specific antibody, and the cytokine-inducing ability of L. casei Shirota. Evaluation of survival after 6 months showed that the number of viable cells in the probiotic flight samples was around 11 log CFU/g, a value comparable to that of ground controls (Sakai et al, 2018). Although these results are very encouraging, additional mechanistic studies under microgravity and simulated space environment are still needed, especially to directly test the health benefits of probiotics in space.…”
Section: Limitations and Next Stepsmentioning
confidence: 80%
See 1 more Smart Citation
“…The authors did not observe differences between the probiotic flight samples and ground controls regarding the profiles of randomly amplified polymorphic DNA, the sequence variant frequency, the carbohydrate fermentative patterns, the reactivity to strain-specific antibody, and the cytokine-inducing ability of L. casei Shirota. Evaluation of survival after 6 months showed that the number of viable cells in the probiotic flight samples was around 11 log CFU/g, a value comparable to that of ground controls (Sakai et al, 2018). Although these results are very encouraging, additional mechanistic studies under microgravity and simulated space environment are still needed, especially to directly test the health benefits of probiotics in space.…”
Section: Limitations and Next Stepsmentioning
confidence: 80%
“…They did not observe differences in growth, survival in simulated gastric or small intestinal juices, or in bacterial gene expression in comparison to control cultures, suggesting that the strain will behave similarly during spaceflight and consequently will maintain its beneficial properties (Castro-Wallace et al, 2017). Recently, Sakai et al (2018) specifically developed a freeze-dried probiotic product for space experiments using the Lactobacillus casei Shirota probiotic strain, and tested its stability over 1 month of storage on the ISS. For the study, a SpaceX/Dragon spacecraft for the 8th commercial resupply mission (SpX-8) was used for the launch to the ISS and return of probiotic samples.…”
Section: Limitations and Next Stepsmentioning
confidence: 99%
“…Based on our observations and previous reports (10), we confirm a mostly human-associated microbiome aboard the ISS (62). Other proposed sources are cargo delivery (due to the detected overlap of cleanroom/ cargo and ISS microbial community), food (such as seasoning, dried fruits, nuts and herbs, or even probiotics (63) (as indicated by the presence of e.g. Bacillus and Lactococcus signatures), and potentially the personal belongings brought to the ISS (possibly reflected by the increased diversity in the personal sleeping unit microbiome).…”
Section: Discussionmentioning
confidence: 99%
“…Los probióticos son preferentes para mejorar el equilibro microbiano intestinal por su capacidad inductora en la conservación del sistema inmune (94,95) . Además, la gravedad artificial, ejercicios físicos de rutina e ingesta normal de alimentos cumplen un papel fundamental en el mantenimiento de la motilidad y equilibrio gastrointestinal (98) .…”
Section: Sistema Digestivounclassified